Evaluation of a pilot reintroduction program for dusky grouper (Epinephelus marginatus) juveniles in inshore marine areas off the southeast Brazilian coast - Claudia Ehlers Kerber; Caio Augusto Perazza; Eric Hallerman; Melissa Sant´Anna; Alexandre Wagner Silva Hilsdorf (Discover Conservation)
Abstract The dusky grouper (Epinephelus marginatus) is a widely distributed epinephelid species. It inhabits the eastern and southwestern Atlantic Ocean, western Indian Ocean, and Mediterranean Sea. Populations of this species have faced significant threats due to various anthropogenic activities, including environmental degradation and intensified fishing effort. To address declining populations, management strategies involving the release of hatchery-reared juveniles have been implemented. This study evaluated the success of a pilot reintroduction program for juvenile dusky grouper by measuring the potential increase in population size in the area. Inshore marine areas along the southeastern Brazilian coast were previously evaluated to determine the best areas for the reintroduction Twenty thousand juvenile dusky groupers (5–10 cm SL) were released at five locations across five selected areas. Assessments were conducted by underwater visual censuses (UVCs) to quantify the presence of juvenile dusky grouper in the selected areas both before and after the releases. Statistical analysis was performed using a Generalized Linear Model (GLM) to estimate the relationship between predictor (number of individuals) and response (release period, depth and sampling points) variables. The results showed a significant increase in juvenile dusky grouper populations at three of the five release areas post-introduction. The methodology employed for stocking dusky grouper juveniles into areas with declining populations demonstrates promise for future conservation efforts aimed at enhancing abundance of this vital marine resource. Results of this research provide valuable insights for the development and implementation of effective conservation programs targeting the recovery of dusky grouper populations.